Factors influencing the acceptance and awareness of permanent method of family planning - Shettian, Nishita; Ajila, Disha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Among developing countries, India holds the second place in being the most populated country accounting to 1.3 billion. This addresses the need for effective population control by implementing various family planning and contraceptive services thereby improving the quality of life. Our study aims at assessing the factors influencing the awareness and acceptance of permanent method of family planning. Methods: This is a questionnaire based cross sectional study carried out in A.J. institute of Medical Sciences on 300 postpartum women who have undergone two or more child births. Results: 77.3% of women were aware of family planning services out of which 64.3% had knowledge about permanent method of sterilization. 73% preferred to undergo tubectomy whereas only 13.7% were willing for vasectomy with the main reason for refusal being fear of surgery (25.9%). 32.6% of women wanted their husbands to undergo vasectomy rather than having a tubectomy themselves. Desire for more children (39%) was the main reason given by most women who refused to undergo tubectomy. Conclusions: Though women were aware of contraceptive practices, proper knowledge about permanent methods of family planning was still inadequate especially regarding vasectomy. Our study showed that lack of awareness and knowledge, fear of adverse effects, fear of sexual dysfunction, culture and religious beliefs, opposition from the male partner and health concerns were the factors influencing tubectomy acceptance over vasectomy as a permanent method of sterilization.